Land transfer and food crop planting decisions in China. Issue 20 (28th November 2021) - Peng, Donghui; Li, Jingrong; Paudel, Krishna; Mi, Yunsheng
ABSTRACT: This paper proposes a theoretical model to illustrate the relationship between the scale of land transfer-in and farmers' crop selection behaviour. We use a semiparametric instrumental variable regression model to test this relationship. Data come from a face-to-face interview survey of 2, 677 farmers located in nine provinces of China collected in 2014–2015. Results show that the size of land transfer-in has a U-shaped impact on the probability of planting food crops. To guarantee food crop self-sufficiency, the Chinese government should encourage land transfer, foster the mobility of agricultural labourers, and enhance the capacity of the rural financial market.